Plan, recruit, retain: a framework for local healthcare organizations to achieve a stable remote rural workforce - Birgit Abelsen; Roger Strasser; David Heaney; Peter Berggren; Sigurður Sigurðsson; Helen Brandstorp; Jennifer Wakegijig; Niclas Forsling; Penny Moody-Corbett; Gwen Healey Akearok; Anne Mason; Claire Savage; et al. (BMC, 2020)
Abstract Background Recruiting and retaining a skilled health workforce is a common challenge for remote and rural communities worldwide, negatively impacting access to services, and in turn peoples' health. The research literature highlights different factors facilitating or hindering recruitment and retention of healthcare workers to remote and rural areas; however, there are few practical tools to guide local healthcare organizations in their recruitment and retention struggles. The purpose of this paper is to describe the development process, the contents, and the suggested use of The Framework for Remote Rural Workforce Stability. The Framework is a strategy designed for rural and remote healthcare organizations to ensure the recruitment and retention of vital healthcare personnel. Method The Framework is the result of a 7-year, five-country (Sweden, Norway, Canada, Iceland, and Scotland) international collaboration combining literature reviews, practical experience, and national case studies in two different projects. Result The Framework consists of nine key strategic elements, grouped into three main tasks (plan, recruit, retain). Plan: activities to ensure that the population's needs are periodically assessed, that the right service model is in place, and that the right recruits are targeted. Recruit: activities to ensure that the right recruits and their families have the information and support needed to relocate and integrate in the local community. Retain: activities to support team cohesion, train current and future professionals for rural and remote health careers, and assure the attractiveness of these careers. Five conditions for success are recognition of unique issues; targeted investment; a regular cycle of activities involving key agencies; monitoring, evaluating, and adjusting; and active community participation. Conclusion The Framework can be implemented in any local context as a holistic, integrated set of interventions. It is also possible to implement selected components among the nine strategic elements in order to gain recruitment and/or retention improvements.